Kennis en houding van verpleegstudente aangaande VIGS in drie opleidingsinstansies in die, Wes-Kaap - M. E. Bester; Y. Arendse (AOSIS, 1996)
A survey was done by means of a questionnaire to obtain information on the knowledge and attitudes of 297 nursing students from three training institutions in the Western Cape regarding HIV-infection and AIDS-patients.